2020
DOI: 10.1002/hrm.22006
|View full text |Cite
|
Sign up to set email alerts
|

The effect of CEO incentives on deviations from institutional norms in foreign market expansion decisions: Behavioral agency and cross‐border acquisitions

Abstract: CEO incentives have been the subject of great interest for human resource scholars. We explore the institutional context within which the CEO makes sense of their incentives. Our theory suggests that CEO equity incentives interact with institutional norms to influence foreign market entry choices. Specifically, we argue that CEOs will weigh the risk bearing created by equity incentives, along with the consequences of legitimacy loss, when deciding whether to deviate from institutional norms when internationali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 141 publications
(176 reference statements)
1
12
1
Order By: Relevance
“…Indeed, audiences may scrutinize and judge a firm's internationalization actions to determine their legitimacy (e.g., Ang, Benischke, & Doh, 2015; Kostova & Zaheer, 1999). Consistent with the theoretical arguments advanced (and empirically supported) by Benischke, Martin, Gomez‐Mejia, and Ljubownikow (2020), our results suggest the existence of a trade‐off between legitimacy risk—that is, “the potential harm to the organization resulting from lack of compliance with institutional norms or expectations” (Benischke et al, 2020, p. 478)—and business risk—that is, “the likelihood of performance failures, or lower than expected returns when the firm makes particular strategic choices under bounded rationality” (Benischke et al, 2020, p. 478). International experience accentuates such a trade‐off, making it more visible and salient.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Indeed, audiences may scrutinize and judge a firm's internationalization actions to determine their legitimacy (e.g., Ang, Benischke, & Doh, 2015; Kostova & Zaheer, 1999). Consistent with the theoretical arguments advanced (and empirically supported) by Benischke, Martin, Gomez‐Mejia, and Ljubownikow (2020), our results suggest the existence of a trade‐off between legitimacy risk—that is, “the potential harm to the organization resulting from lack of compliance with institutional norms or expectations” (Benischke et al, 2020, p. 478)—and business risk—that is, “the likelihood of performance failures, or lower than expected returns when the firm makes particular strategic choices under bounded rationality” (Benischke et al, 2020, p. 478). International experience accentuates such a trade‐off, making it more visible and salient.…”
Section: Discussionsupporting
confidence: 86%
“…Our microfoundations perspective allows us to point out the contribution of the board to a firm's information processing and hence to shed new light on the role of the board in internationalization and mimetic processes. While previous research has shown that these board-level factors have a direct effect on firms' global strategies (e.g., Barroso, Villegas, & Pérez-Calero, 2011;Benischke et al, 2020), in our study we show their moderating effect through their interaction with international experience. Relatedly, the extant literature shows the influence of the board on the imitation of peers' strategic actions (e.g., Ang et al, 2018;Haunschild, 1993), including their location choices (e.g., Connelly et al, 2011).…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…When a problem is framed as “negative,” decision-makers often take more aggressive risk behaviors to minimize the loss of their wealth. Behavioral agency model has been extensively used to explain decision-makers’ risk preferences and associated organizational performance since it is proposed (e.g., Martin et al, 2015 ; Poletti-Hughes and Briano-Turrent, 2019 ; Benischke et al, 2020 ). But this model used into the innovation research is still lacking.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…In this regard, it not only makes up the deficiency of classic agency model, but also expands the research of prospect theory. Since its inception, the behavioral agency model has been widely used to explain the relationship between executive risk preferences and organizational outcomes (e.g., Martin et al, 2015 ; Poletti-Hughes and Briano-Turrent, 2019 ; Benischke et al, 2020 ). But this model used into the innovation research is still lacking.…”
Section: Introductionmentioning
confidence: 99%